The correlation between students’ reading speed and their reading comprehension - Syuqaira El Humaira; Endang Komariah; Nurul Inayah (Research in English and Education Journal, 2017)
This research is aimed to find out if there is a significant correlation between the reading speed of the XII grade students at SMA Negeri 3 Banda Aceh with their reading comprehension. The population for this study were all students of class XII at SMAN 3 Banda Aceh. By using the random sampling, the researcher chose 31 students of class XII MIPA 6 as the sample. The data was collected by using reading speed and reading comprehension test. After the data was collected, the correlation data is processed using product moment formula. The rXY result achieved to 0.74. The result reveals that the rvalue, 0.74, was higher than the  rtable, 0.355. Referring to the table at significant level 0.05, the result means that there is a significant correlation between students’ reading speed and their reading comprehension.